2016
DOI: 10.1007/s10549-016-3972-z
|View full text |Cite
|
Sign up to set email alerts
|

ANG1005 for breast cancer brain metastases: correlation between 18F-FLT–PET after first cycle and MRI in response assessment

Abstract: ANG1005 warrants further study in BCBM. Results demonstrated a moderately strong association between MRI and F-FLT-PET imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 31 publications
0
23
0
1
Order By: Relevance
“…Specific PET tracers such as the monoclonal antibody 89 Zrtrastuzumab are able to detect brain metastases in HER2 + breast cancer with a good uptake-to-background ratio (Dijkers et al, 2010). For breast cancer brain metastases treated with paclitaxel covalently linked to angiopep-2, changes in FLT PET correlated with MRI findings in a pilot study of 10 patients after a single treatment cycle and appeared to correlate with outcome (O’Sullivan et al, 2016). Extracranially, changes at 3 weeks in HER2+ patients correlate with tumor response at 8 weeks as measured by CT; this is not true for FDG PET (Gaykema et al, 2013).…”
Section: Early Response Markersmentioning
confidence: 89%
“…Specific PET tracers such as the monoclonal antibody 89 Zrtrastuzumab are able to detect brain metastases in HER2 + breast cancer with a good uptake-to-background ratio (Dijkers et al, 2010). For breast cancer brain metastases treated with paclitaxel covalently linked to angiopep-2, changes in FLT PET correlated with MRI findings in a pilot study of 10 patients after a single treatment cycle and appeared to correlate with outcome (O’Sullivan et al, 2016). Extracranially, changes at 3 weeks in HER2+ patients correlate with tumor response at 8 weeks as measured by CT; this is not true for FDG PET (Gaykema et al, 2013).…”
Section: Early Response Markersmentioning
confidence: 89%
“…Both peptides have already been extensively used in efforts to deliver drugs to gliomas [25,27]. ANG1005, a drug composed of paclitaxel covalently linked to An2, has been tested against brain metastases of breast cancer [40,41] and is undergoing other clinical trials. PAPTP and PCARBTP efficiently killed cultured glioma and glioblastoma cell lines but did not affect tumor growth in an orthotopic murine model [16].…”
Section: Introductionmentioning
confidence: 99%
“…As a marker of proliferation, FLT seems to be useful in further evaluating the activity of metastatic brain lesions. O’Sullivan et al reported that there was quite a good correlation between FLT and MRI in assessing treatment responses using a novel agent for breast cancer derived brain metastatic disease and demonstrated the supporting valuable contribution of FLT-PET in these cases [16]. Compared to FDG in head and neck cancer and thoracic malignancies, FLT seems to perform better in metastatic intracranial lesions [17,18].…”
Section: Discussionmentioning
confidence: 99%